A conversation on academic freedom and freedom of expression at the university - Robert C. Post; Jordi Pujol (Church, Communication and Culture)
In this academic interview, Yale law professor Robert C. Post elucidates the distinction between freedom of expression and academic freedom, emphasizing that universities are communities guided by the twin missions of education and knowledge production. At their best, universities function as ‘disciplinary communities’ who must act in professionally competent ways. Post characterizes academic freedom as a ‘two-faced coin’. On the one hand, academic freedom embodies the values and principles essential for the governance of a healthy university community; on the other hand, it shields universities from external regulations that might hinder their mission of advancing education and research. Post also addresses the significant challenges to freedom of expression posed by the cosmopolitan public sphere, particularly in the age of social media and AI. As a trustee of Meta’s Oversight Board, Post highlights the complex issue of harmful speech online, noting that it is not only a matter of scale but also of scale, producing harms that are stochastic in nature.